Explaining the Existence of Lightning: Literature Review and an Example of Calculating the Efficiency Value of a Detection System - Goeritno, Arief; Azama, Irham Muhammad (Master Program in Mechanical Engineering, Gunadarma University, 2024)
The existence of lightning as atmospheric electricity should be thoroughly reviewed concerning the process of going over a subject again in a study that can explain its existence. A review in the form of presenting the State-of-the-Art (SotA) of the existence of lightning with objectives is examined, which includes the description of (i) the forming Cumulonimbus (Cb) clouds and lightning generation; (ii) the principles of electromagnetic field measurement; and (iii) the lightning strike detection systems and an example of calculating the efficiency value. A researcher's algorithm for carrying out the study takes the shape of achievement and adherence to explain in the form of literature reviews. Therefore, a flowchart based on the form algorithm can be created. The results and discussion of three main things related to explaining the existence of lightning as atmospheric electricity include forming Cb cloud and lightning generation, electromagnetic field measurement principles, and lightning strike detection systems, which are equipped with an example of calculating the efficiency value. Based on the discussion of three main things, it can be concluded that explanations of many kinds of literature reviewed can elaborate an understanding of the existence of lightning.